Hybrid Soft Robot Hand - Buserah, Rahmat; Ribuan, Mohamed Najib (Evolution in Electrical and Electronic Engineering, 2022)
Developing a hybrid soft robot hand from soft and hard materials is one of the new innovations in robot hand technology. Most of the common robot hand nowadays is rigid that influenced less dexterity and compliance. In this research, the Hybrid soft robot hand prototype is designed to focus on mechanical actuation.  The model is based on Asian size and designed using SolidWorks. The prototype is fabricated using Thermoplastic polyurethane (TPU) for hard material and Polylactic Acid (PLA) for soft material before being installed with the electrical part. The complete prototype was tested and underwent dexterity experiments like gripping objects and bending each finger. The results show the thumb finger achieved a maximum bending angle of 158.35 degrees, and the middle finger achieved a minimum bending angle of 122.957 degrees.